Benefits of electrical/electromagnetic stimulation for human motor system - Shlyakhtov, V. N. (Theory and Practice of Physical Culture, 2019)
In addition to educational tools, a range of stimulation methods are used for physical fitness and coordination improvement purposes including: biomechanical muscle stimulation; electrical stimulation of muscles and peripheral nerves; and the electromagnetic stimulation of the spinal cord and muscles, with all these methods applied to complement the training systems. Objective of the study was to rate benefits of electrical/ electromagnetic stimulation for human motor system. Sampled for the study were the 18-27 years old individuals (n= 48). The experiment was intended to rate the moment of force gradient, the H-reflex and the M-responses under growing power and frequency of electromagnetic and electrical impulses on the peroneal nerve; and profile variations of the above rates in the 10-day electromagnetic stimulation of the calf muscle in foot flexing exercises; plus variations of the running stride coordination structure in the 10-second top-speed treadmill practice with the continuous electrical stimulation of the lumbar spinal cord. The moment of force gradient for the top-intensity electrical stimulation was tested to exceeded by 185.5% the rate induced by the electromagnetic exposure. The highest moment of force was achieved at 25 Hz. The above 10-day electromagnetic stimulation was tested to increase the maximum moment of force in the EG by 52.3% versus the pre-experimental rate in RG that grew by 24.1%. The electrical stimulation of the spinal cord in the treadmill exercise was tested to boost the electromyographic activity of the hip flexors by 35.3%, whilst the anterior tibial muscle activity, on the contrary, was tested to drop by 10.7%. The study data contribute to the knowledge of the electrical stimulation and electromagnetic stimulation effects on the spinal cord and muscular performance.